Support to Classify Intercollegiate Athletics Participation as a High Impact Practice - Molly Harry (University of Kansas Libraries, 2023)
Abstract: Academic practitioners have promoted the idea of high impact practices (HIPs) in higher education. HIPs are cognitive and social activities designed to prepare students for life after college. Research indicates that college athletes are less involved in HIPs than non-athlete peers; however, limited research has explored the ways in which athletics, if organized and governed appropriately and ethically, can qualify as a HIP. This manuscript examines the intercollegiate athletics and higher education literature and provides key ways in which athletics participation has components-such as reflection, intentionality, and interaction-present in HIPs. Additionally, this manuscript offers practical implications for athletics leaders to consider in order to further align athletics participation with other traditional HIPs. As critics note the growing divide between academics and athletics, reframing sports as an educational endeavor, such as a HIP, may help alleviate some strain between sport and the academy.